Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1097/upj.0000000000000428.01
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Comment

Abstract: 4. Summaries of Clinical Trial Results for Laypersons. 2023. https:// health.ec.europa.eu/system/files/2020-02/2017_01_26_ summaries_of_ct_results_for_laypersons_0.pdf 5. Good Lay Summary Practice. 2023. https://health.ec.europa.eu/ system/files/2021-10/glsp_en_0.pdf 6. Shiely F, Daly A. Trial lay summaries were not fit for purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Although studies report that LLM responses are often difficult to read ( 4 ), patients can ask LLMs to simplify their language output or to expand on other topics. Unlike standard informational brochures or pamphlets, these models can tailor their responses based on individual queries, ensuring that each patient receives information most pertinent to their concerns ( 5 , 6 ). For example, a patient can interact with LLMs by typing “I still don’t understand this procedure, can you explain it?” or “explain it to me in simple 8th grade terms” until they are satisfied with an answer.…”
Section: Llms: More Than Just Machinesmentioning
confidence: 99%
“…Although studies report that LLM responses are often difficult to read ( 4 ), patients can ask LLMs to simplify their language output or to expand on other topics. Unlike standard informational brochures or pamphlets, these models can tailor their responses based on individual queries, ensuring that each patient receives information most pertinent to their concerns ( 5 , 6 ). For example, a patient can interact with LLMs by typing “I still don’t understand this procedure, can you explain it?” or “explain it to me in simple 8th grade terms” until they are satisfied with an answer.…”
Section: Llms: More Than Just Machinesmentioning
confidence: 99%
“…These programs are rapidly evolving, and their knowledge could be used as a resource in many fields [6]. However, the consensus to use LLMs as a tool in medicine has not yet been achieved, as the reliability of the information they provide is not yet fully understood [6][7][8]. As such, previous studies of AI performance in medical examinations have found varying and contradicting results [9][10][11].…”
Section: Introductionmentioning
confidence: 99%